2022
DOI: 10.1111/adb.13143
|View full text |Cite
|
Sign up to set email alerts
|

Repeated low doses of LSD in healthy adults: A placebo‐controlled, dose–response study

Abstract: The resurgence of interest in using psychedelic drugs, including lysergic acid diethylamide (LSD), in psychiatry has drawn attention to the medically unsupervised practice of 'microdosing'. Thousands of users claim that very low doses of LSD, taken at 3-4-day intervals, improve mood and cognitive function., However, few controlled studies have described the effects of the drug when taken in this way. Here, in a double-blind controlled study, we studied the effects of four repeated doses of LSD tartrate (13 or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 45 publications
1
42
0
Order By: Relevance
“…The studies included in our analysis vary greatly with regards to experimental setting. Bershad et al (2019) reports of “living-room style” environments with possibilities to relax, read or watch movies between measurements [44], similar to Preller et al (2017) (“in an esthetic living-room-like room”) [35] and de Wit et al (2022) [45]. In other studies, however, participants were also given tasks during LSD applications that involved greater effort, potentially inhibiting the manifestation of certain effects [75].…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…The studies included in our analysis vary greatly with regards to experimental setting. Bershad et al (2019) reports of “living-room style” environments with possibilities to relax, read or watch movies between measurements [44], similar to Preller et al (2017) (“in an esthetic living-room-like room”) [35] and de Wit et al (2022) [45]. In other studies, however, participants were also given tasks during LSD applications that involved greater effort, potentially inhibiting the manifestation of certain effects [75].…”
Section: Discussionmentioning
confidence: 94%
“…For instance, visual phenomena (11-ASC: Audio-Visual Synesthesia, Complex and Elementary Imagery ) show an x-axis intercept at around 10 μg, and at 20 μg reach around 10% of the maximum score. These effects are unlikely due to placebo effects, as those of the given studies which included a placebo condition reported only negligible effects [22,26,28,35,39,4345,6669]. However, these estimates are strongly influenced by the fact that multiple studies investigated dosages below 20 μg, while there are no studies available in the dosage range from 20 to 50 μg, resulting in an overestimation of the curves slope at their onset.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of clinical microdosing studies tested single LSD doses (e.g., Bershad et al, 2019Bershad et al, , 2020Greiner, 1958;Hutten et al, 2020;Murray et al, 2021). Only two multiple-dose studies have been reported, with schedules consisting of a placebo, 5, 10, or 20 µg every 4th day over a 21-day period (Family et al, 2020;Yanakieva et al, 2019) and placebo, 13, or 26 µg LSD tartrate (equivalent to 10 or 20 µg LSD) once every 3 to 4 days for a total of four doses (de Wit et al, 2022). No cardiovascular-related adverse events were reported in either study, and no ECG abnormalities were observed in the study by Family et al However, several months of chronic dosing is typically needed for VHD symptoms to emerge (Elangbam, 2010), so these dosing periods were too short to assess possible VHD, especially with no echocardiography assessments.…”
Section: In Vivo Lsd Studiesmentioning
confidence: 99%